2007
DOI: 10.4161/cc.6.3.3834
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Centrosome Amplification in Radiation-Induced Mitotic Catastrophe

Abstract: Cells exposed to ionizing radiation die via different mechanisms, including apoptosis and mitotic catastrophe. To determine the frequency of mitotic catastrophe in tumor cells after irradiation, we used time-lapse imaging to track centrin-1 and histone H2B in U2OS osteosarcoma cells. We observed a dose-dependent increase in the frequency of mitotic catastrophe after irradiation, although a consistent 30% of cell death occurred through mitotic failure at doses from 2-10 Gy. One potential cause of mitotic catast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 42 publications
4
60
0
Order By: Relevance
“…The formation of multinuclear cells and multipolar spindle in cells after DNA damage is the characteristic of cells undergoing mitotic catastrophe (18,35,36). Using time-lapse video microscopy, we aimed to detect the association between DNA-PKcs deficiency and mitotic catastrophe in response to DNA damage.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of multinuclear cells and multipolar spindle in cells after DNA damage is the characteristic of cells undergoing mitotic catastrophe (18,35,36). Using time-lapse video microscopy, we aimed to detect the association between DNA-PKcs deficiency and mitotic catastrophe in response to DNA damage.…”
Section: Resultsmentioning
confidence: 99%
“…For live cell imaging, cells were stably transfected with a pmRFP-N1-H2B, which encodes red fluorescent protein (RFP)-tagged histone H2B. 51 Before imaging, cells were cultured in media supplemented with 12.5 mM Hepes (pH 7.5) in poly-D-lysine-coated dishes (MatTek) for 3 h. Time-lapse images were acquired for 3h at 3 min intervals on a DeltaVision integrated microscope system using a PlanApo N60× oil objective (N.A. 1.42) and a WeatherStation environmental chamber at 39.5°C (Precision Control).…”
Section: Methodsmentioning
confidence: 99%
“…i) Recent studies have shown that several DNA repair proteins localize to the centrosome, and defects in these proteins cause several functional aberrations in centrosomes such as centrosome amplification. [40][41][42][43] Also, it has been shown that DNA damage can induce centrosome amplification. [41][42][43] Overexpression of Usp1 in NIH3T3 cells inhibited UV-induced Fancd2-Ub and PCNA-Ub (Fig.…”
Section: Discussionmentioning
confidence: 99%